Self-regulated learning in technology enhanced learning environments a European perspective - Carneiro, Roberto; Lefrere, Paul; Steffens, Karl; Underwood, Jean (SensePublishers, 2011)
Self-regulated learning (SRL) subsumes key aspects of the learning process, such as cognitive strategies, metacognition and motivation, in one coherent construct. Central to this construct are the autonomy and responsibility of students to take charge of their own learning. Skills for self-regulation can be encouraged both directly and indirectly through a range of learning activities. In this book we look specifically at the ways in which technology enhanced learning environments (TELEs) have been used to support self-regulation. The book provides an overview of recent studies on SRL in TELEs in Europe ? a perspective which is new and has not been articulated hitherto. It addresses conceptual and methodological questions as well as practices in technology enhanced learning. While the focus is on European studies, we are aware that much of the groundwork in the field of SRL has emanated from the United States. The book is divided into three parts: (A) Foundations of SRL in TELEs, (B) Empirical studies on SRL in TELEs and (C) SRL in TELEs: perspectives on future developments. The book presents a rich resource of information for researchers and educators at all levels who are interested in supporting the acquisition of SRL through TELEs.